The Potential of Narrative for Understanding Protein Biosynthesis in the Context of Viral Infections - Jörg Zabel; Cornelia Averdunk (MDPI AG, 2024)
Based on the assumption that the process of understanding is partly narrative, this study explores the potential benefits and limitations of using narrative writing in biology education. We investigate what contribution a student-centered narrative intervention can make to the conceptual understanding of protein biosynthesis in the context of viral infections and virus replication. After a teaching sequence on this topic, 68 secondary school students (M = 15.7 years, SD = 0.57 years) explained virus replication in a written text. One subsample (n = 46) was instructed to write a narrative text, while the other one (n = 22) was asked to write an expository (non-fictional) text. Our data analysis encompassed an analysis of the structural narrativity in the student texts, as well as a concept-related rating of the level of scientific correctness in three categories. A post-test questionnaire (35 items) was used to depict the learners' viewpoints on their respective text production and the learning process that they experienced. Our findings indicate that most learners actually produced the text type they were supposed to, with exceptions in both sub-samples. As to the level of concept-related scientific correctness, we found no major differences between the two interventions. However, for two concepts, compartmentalization and levels of organization, the data indicate the significant advantage of the narrative intervention. We conclude from our results that to some extent, the effective learning properties of narrative texts, derived from the theoretical foundations, could indeed successfully be demonstrated in the field of virus replication. However, narrative text production is not equally beneficial for all aspects of the biological topic, and it also poses specific problems for some learners.